PENGARUH CURRENT RATIO DAN TOTAL ASSET TURN OVER TERHADAP LEVERAGE IMPLIKASI PADA KINERJA PERUSAHAAN PADA PT SEMEN INDONESIA TBK PERIODE 2014 – 2023 - Hendrika Frans Telaumbanua; Amirudin (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of current ratio and total assets turnover on leverage on firm performance of PT Semen Indonesia, Tbk for the period 2014 - 2023, either partially or simultaneously. The method used is quantitative method. The sample used is in the form of financial statements of PT Semen Indonesia, Tbk for 10 years. The sampling technique used is purposive sampling technique. The results of this research indicate that the Current Ratio partially has a negative effect on leverage t_count < t_table (1,070141 < 2,36462) with Sig. ,.05 or (0,3201 > 0,05), the Total Assets Turnover variable partially has a positive effect on leverage t_count < t_table (-2,504065 < 2,36462) with Sig. 0,05 or (0,0407 < 0,05). Simultaneously Current Ratio and Total Assets Turnover on leverage with the results F_count > F_table (4,969995 > 4,76) with significant profitability sig. 0,05 or 0,045357 < 0,05. The results of this study indicate that the current ratio partially negatively affects the performance of the company t_count < t_table (0,872101 < 2,36462) then the significant value of profitability > sig. 0,05 or (0,4167> 0,05). In the total assets variable, turnover has a partial positive effect on t_count > t_table (4,964052> 2,36462) then a significant value on profitability < sig. 0,05 or (0,0025 <0,05). The results of the study simultaneously Current Ratio and Total Assets Turnover simultaneously have a significant effect on Debt to Equity Ratio with the results of F_count > F_table (4,969995> 4,76) with significant profitability < sig. 0,05 or (0,045357 <0,05). The results of research on Current Ratio and Total Asset Turnover, Debt to Asset Ratio simultaneously have a significant effect on Return on Assets with the results of F_count > F_table (20,71012> 4,76) with significant profitability < sig. 0,05 or (0,001444 <0,05). The results of the coefficient of determination research obtained results of 0,9154, which means that it identifies the independent variable in explaining the dependent variable 91,19% and the remaining 8,81% is explained by other variables not explained in this study.